The angel maker : a novel [large type] - North, Alex, 1976- (Thorndike Press large print basic, 2023)
"Katie Shaw lived a charmed life. Until the day a violent stranger changed the fate of her family forever. Years later, still unable to live down the guilt surrounding what happened to her brother, Chris, Katie struggles to separate the real threats from the imagined. Then she gets the phone call: Chris has gone missing. Meanwhile, Detective Laurence Page is facing a particularly gruesome crime. A distinguished professor has been brutally murdered just hours after firing his staff. All the leads point back to two old cases: the gruesome attack on teenager Christopher Shaw, and the crimes of a notorious serial killer who, legend had it, could see the future"--